Effect of temporal lakes on avifaunal composition at the Southeast of Isthmus of Tehuantepec, Oaxaca, Mexico - Rioja-Paradela, Tamara (Universidad de Costa Rica, 2014)
Oaxaca hosts one of the greatest biodiversity in México, occupying first place in avian diversity compared to other regions of the country. However, the area is undergoing serious problems such as high deforestation rates, soil erosion and over exploitation and extinction of species. These factors have all contributed to the current loss of biodiversity. Also, biological inventories are still incomplete. One of the least explored sites is the semiarid zone of Tehuantepec isthmus, around the locality of Santa Maria del Mar, Oaxaca, México. The area includes floodable grasslands, mangrove areas and dry forest, providing a range of potential habitats for different species. Our objective was to evaluate the effect of temporal lakes on spatial and temporal composition of the avifauna in Santa Maria del Mar, in order to generate information regarding this group within the region and the state, and to understand the importance of flood areas for resident and transitory birds. We conducted 12 avifauna surveys between July 2006 and June 2008, and established two transects of 2km length in each of four habitat types (beach, grassland, dry forest, and mangrove). We found a total of 75 species, corresponding to 16 orders and 30 families. Within an area of 26km2, we significantly found 10.1% of the total number of bird species recorded for the entire state, and 6.6% of the total reported in Mexico. The families most represented were: Ardeidae, Laridae and Scolopacidae. Over the entire study period, dry forest was the most diverse habitat; followed by mangrove, grassland and the beach. Of all the species recorded, 38.6% were found at the edge or in the temporal lakes. We found a significant difference in species composition between seasons in the grassland, but no difference in the other habitats. Our results showed a significant effect of temporary lakes on avian diversity during the wet season; it also demonstrated the importance of grassland conservation given its relevance for presence of waterbirds. We suggested a continued and more intense monitoring; and proposed the designation of the area as an Important Conservation Bird Area (AICA). Tamara Rioja-Paradela1,2, Arturo Carrillo-Reyes1,2 & Eduardo Espinoza-Medinilla1 1Sustentabilidad y Ecología Aplicada, Universidad de Ciencias y Artes de Chiapas. Libramiento Nte. Pte. 1150, Col. Lajas Maciel, Tuxtla Gutiérrez, Chiapas, México; tamararioja@gmail.com, arturocarrilloreyes@gmail.com, eduardo.espinoza@unicach.mx2Oikos: Conservación y Desarrollo Sustentable, A.C., Bugambilias 5, Col. Bismark, San Cristóbal de las Casas, Chiapas, México